A 9-year controlled prospective neuropsychological assessment of amateur boxing - Porter, M. D. (Clinical Journal of Sport Medicine, 2003)
Objective: To test the hypothesis that there is an association between amateur boxing and chronic traumatic encephalopathy using neuropsychologic assessments.